'If You Can Make it Here, You Can Make it Anywhere': Performance Management and PlaNYC Climate Change Initiatives. Issue 4 (2nd April 2016) - Jones, Stephen
Abstract : Jones S. 'If you can make it here, you can make it anywhere': performance management and PlaNYC climate change initiatives, Regional Studies . This paper investigates the contribution of performance management in implementing climate initiatives introduced by the Bloomberg administration in New York City. PlaNYC has been praised as one of the most significant climate change initiatives by a city government as it included measurement protocols and a performance management framework to provide evidence for policy and management change. This paper develops an assessment framework and takes a case study approach to examine the context and implementation of PlaNYC from 2007 to 2013. The analysis provides insights for other city governments developing and implementing climate change policies.